Refleksi Tentang Makna Salib dan Penderitaan Manusia dalam Terang Ensiklik Salvifici Doloris - Alfons Seran; Ola, Dominikus Doni; Zamili, Alberta Animarwati (Journal New Light, 2025)
This article aims to deeply reflect on the meaning of suffering and the cross in the light of Christian faith, as elaborated in the Encyclical Salvifici Doloris by Pope John Paul II. Suffering is an inevitable part of every human life. It should not be viewed merely as a negative experience or a painful burden, but also as a path that can lead one to a deeper understanding of faith and a closer relationship with God. The method used is the library research method, by collecting and analyzing various written sources such as books, scholarly journals, Church documents, and credible references from the internet. This approach aims to provide a strong theoretical foundation while also exploring various thoughts and recent findings relevant to the theme of this thesis. The findings of this study show that human suffering, when united with the suffering of Christ on the cross, has redemptive value and becomes a means of participating in God's work of salvation. This research concludes that, in the light of Christian faith, suffering holds a deeper meaning than simply being a painful experience. Suffering is not merely something to be endured, but also a way to participate in God’s salvific work and a means to lead humanity into a more intimate communion with Him.